Complicated congenital malaria due to Plasmodium vivax - Angélica María Díaz-Contreras; Germán Camacho-Moreno; Édgar Rojas-Soto (Case Reports)
Congenital malaria is a disease that appears in the neonatal period and that, if not treated in a timely manner, may have fatal consequences for the newborn. According to statistics published in The State of the World Children 2009 Report, 3.7 million children under the age of 28 days die annually around the world at present. 8% of cases correspond to children under 5 years of age with malaria (1). Similarly, studies in endemic areas have reported incidences of congenital malaria of between 0.83 and 5.93% (2). Here, we present a case of congenital malaria in a one-month-old nursing infant whose mother received treatment for malaria from Plasmodium vivax (P. vivax) during gestation but suffered a relapse with a consequent compromise of the infant in utero. There is a need to recognize the high prevalence of this disease in our context and to know how to monitor and treat the disease in special cases like those of gestating mothers and newborn infants with congenital infections.